The Influence of Urban Spatial Configuration and Physical Environment of Street Space on Pedestrian Behaviour, Case Study: Shah Alam (SACC Walk) and Kuala Lumpur (Kasturi Walk) - Nadhirah, Nordin; Ishak, Che Abdullah; Imanina Alhusna, Mat Setia; Yusfida Ayu, Abdullah; Khalid, Zanudin (Malaysian Institute of Planners (MIP), 2025)
The global phenomenon of climate change has urged countries to take action and measures toward a more sustainable and green approach. Malaysia is one of the countries that is now slowly making its steps towards more sustainable development with a greener approach. Encouraging active transportation and providing a sufficient pedestrian environment can help reduce dependency on vehicles, further improving the environment in a sustainable manner. This research intends to study pedestrian behaviour in two different cities, Shah Alam and Kuala Lumpur, focusing on a smaller context of streets. The objectives of this study are, firstly, to study the correlation between urban spatial configuration and pedestrian behaviour. Secondly, to study the relationship between physical attributes of street space and pedestrian behaviour. Thirdly, to propose recommendations that encourage foot mobility in the research area. This research employed a mixed-method approach. The quantitative data is presented using the global (Rn) and local integration (R3) values using axial line analysis, whereas the qualitative data is used to collect Social variables represented as Necessary, Optional and Resultant (N, O, R) for pedestrian behaviour and Social-Physical variables represented as Street Element, Building Element and Landuse Element (SE, BE, LE) for physical environment. The results are then presented using descriptive analysis and behavioural mapping from direct observation based on these variables. The main findings of this research paper conclude three main findings. First, the analysis of spatial configuration using the axial lines map showed that the R3 value is higher for Kasturi Walk, predicting it as a highly accessible street to pedestrians. Second, the spatial configuration and pedestrians do have a highly significant correlation with a p-value of 0.003. Third, SE, BE, and LE are the main factors that drive the behaviour of static and dynamic pedestrian activities. As a conclusion, this study uncovered the factors influencing pedestrian behaviour in Shah Alam and Kuala Lumpur. It is fundamental that further research needs to be done with a larger sample size with more streets to establish a stronger understanding and importance of this study. This study is useful for local authorities and policymakers to improve placemaking strategies and urban design as well as establish more pedestrianised streets.